Meningkatkan Literasi pada Siswa Siswi SD Negeri Grogol Utara 09 melalui Kegiatan Festival - Deni Arya Saputra; Jamiati KN (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
Literacy is a vital aspect of education to ensure students' abilities in comprehending, interpreting, and interacting with various forms of texts. This study aims to evaluate the effectiveness of festival activities as a strategy to enhance students' literacy at SD Negeri Grogol Utara 09. A case study method was utilized to analyze the impact of festival activities on literacy skills, with 50 students from grades IV and V participating. Festival activities included film screenings, poetry readings, and dance performances, with data collection conducted through observation, interviews, and questionnaires before and after the events. Data analysis revealed a significant improvement in students' reading, writing, and speaking skills after engaging in festival activities. Additionally, students' interest in literacy and creative expression also increased positively. These findings affirm that festival activities can serve as an effective means to expand students' literacy beyond conventional curricula, providing a meaningful contribution to holistic education.